Application of stable isotopic and mineral elemental fingerprints in identifying the geographical origin of concentrated apple juice in China. (15th October 2022) - Liu, Xiaohan; Mu, Jian; Tan, Dan; Mao, Kemin; Zhang, Jinjie; Ahmed Sadiq, Faizan; Sang, Yaxin; Zhang, Ang
Highlights: Chinese concentrated apple juice was classified to verify origin. Combination of stable isotopic and mineral elemental improved model performance. PLS-DA models were used for evaluation. The key variables tracing the origin of Chinese concentrated apple juice were identified. Abstract: Food traceability is an important component of food safety and quality. Currently, there is no authentic established technique to identify the origin of concentrated apple juice (CAJ) in China. In this study, the isotopes of δ 13 C, δ 18 O and the contents of 32 elements in CAJ from five production areas (BHB, NWR, SCH, LP and YRAR) were determined. The δ 13 C, δ 18 O and 28 elements were significantly different (P < 0.05: post-hoc Duncan's test) in the five production areas. PCA, PLS-DA and OPLS-DA were employed for regional classification of samples. The results show that ten key variables (Tl, Se, δ 18 O, B, Mg, Sr, Nd, Mo, As, and Na) are more relevant for discrimination of the samples. These findings contribute to understanding the variations of stable isotopic and element compositions in Chinese CAJ depending on geographic origins and offer valuable insight into the control of fraudulent labeling regarding the geographic origins of CAJ.